Clinical relevance of the hip joint: Part II–Importance of joint distraction. (2nd January 2016) - Sato, Tomonori; Sato, Naomi
Abstract : Osteoarthritis (OA) is the most common degenerative disease affecting the hip (hip OA). It is characterized by symptoms such as stiffness and pain, and results in restricted range of motion, cartilage destruction, decreased joint space width, and reduction in activities and quality of life. However, there is no adequate conservative treatment for hip OA. One of the key factors for managing hip OA is unloading or distracting the joint with traction force. Joint distraction with a surgical procedure has been used to treat OA, mostly in the knee and the ankle joints, and the effects of joint distraction on joint structure and clinical symptoms have been reported. Here, we briefly review OA and then discuss the potential benefit of distraction of the hip joint in management of OA, focusing on conservative methods.